The Safety of Fat Grafting: An Institutional Retrospective Review. (June 2022) - Fang, Hua Amanda; Soto, Edgar; Pigg, Ricky; Smith, Metta; Boyd, Carter J.; Ananthasekar, Shivani; Fix, R. Jobe; Kilic, Ali; Denney, Brad; Patcha, Prasanth; Myers, René P.; de la Torre, Jorge I.; et al.
Abstract : Background: Autologous fat grafting is a popular technique for volume replacement in the breast and face. The efficacy, safety, and complication rate of this technique at the division of plastic surgery at the University of Alabama at Birmingham will be described in this review. Methods: An institutional review board–approved retrospective review of patients undergoing fat grafting procedures from January 2015 to July 2018 was performed. Records were reviewed for fat graft recipient site, donor site, amount grafted, and complications. Continuous variables were compared using either a t test or one-way analysis of variance test. Categorical data were compared using χ 2 test. A P value of 0.05 or less was considered statistically significant for all comparisons. Results: A total of 396 patients who underwent fat grafting procedures of the face and body from January 2015 through July 2018 met inclusion criteria. Average amount of fat grafted for all grafts was 124.4 +/− 6.74 grams. Two hundred fifty of the grafts (62.7%) involved the bilateral breasts with an average of 140.6 +/− 93.97 g used, 70 per side. Of the 396 patients, 110 (27.8%) experienced complications. Forty three of the complications (10.9%) were considered to be major, which included hematomas/seromas, fat necrosis, dermatitis/cellulitis, and infection. No statistical differences were seen among recipient site complication rate. Types of minor complications were statistically significant per recipient sites with bilateral breasts more likely to experience asymmetry than the other recipient sites (20% for bilateral breasts vs 16% overall, P < 0.05). Fifty nine of the 110 patients (53.6%) had the complications reported to be resolved. Conclusions: Fat grafting is a reliable method for volumization of the breasts and face. Minor complications were not infrequent in this case series; however, no life-threatening complications were observed. Continued work needs to be done to use fat grafting beyond traditional measures.